The Traps of the European Union Governing: Deficits of Normative and Social Legitimacy - Alina Struguţ (Romanian Journal of European Affairs)
The purpose of this essay is to investigate the various dimensions that indicate deficiency in the normative and social legitimacy at the level of the EU governing. The approach is structured on a theoretical framework defining the conceptual understanding of these notions and an analytical one where the focus will be on identifying different traps/impediments within the EU governance, which motivate these deficiencies.